2010
DOI: 10.1590/s0100-06832010000200009
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of two plant growth-promoting bacteria from the rhizoplane of a legume (Lupinus albescens) in sandy soil

Abstract: SUMMARYTwo bacterial strains that amplified part of the nifH gene, RP1p and RP2p, belonging to the genus Enterobacter and Serratia, were isolated from the rhizoplane of Lupinus albescens. These bacteria are Gram-negative, rod-shaped, motile, facultative anaerobic, and fast-growing; the colonies reach diameters of 3-4 mm within 24 h of incubation at 28 °C. The bacteria were also able to grow at temperatures as high as 40 °C, in the presence of high (2-3 % w/v) NaCl concentrations and pH 4 -10. Strain RP1p was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…Mucus production probably represents a mechanism of rhizobia adaptation and endurance in hostile climatic and edaphic conditions. It prevents desiccation of the bacteria and helps them withstand fluctuations in temperature, salinity, and acidity [ 40 ]. Batista et al [ 41 ] noted increased production of mucus in isolates of Bradyrhizobium as a mechanism of adaptation to acid soils of Cerrado region in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Mucus production probably represents a mechanism of rhizobia adaptation and endurance in hostile climatic and edaphic conditions. It prevents desiccation of the bacteria and helps them withstand fluctuations in temperature, salinity, and acidity [ 40 ]. Batista et al [ 41 ] noted increased production of mucus in isolates of Bradyrhizobium as a mechanism of adaptation to acid soils of Cerrado region in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA fragments were amplified by PCR using the enterobacterial repetitive sequence BOX A1 primer (Versalovicj et al 1994). Reactions were performed according to Giongo et al (2010). The resulting DNA fingerprints were transformed into a binary matrix and subjected to a diversity analysis using the UPGMA algorithm and the Jaccard coefficient using the PAST software (Hammer et al 2001 The seven selected native isolates were identified at the genera level by partial 16S rRNA gene sequencing.…”
Section: Genetic Diversity Of Bacterial Isolatesmentioning
confidence: 99%
“…Nos trabalhos brasileiros as pesquisas sobre as interações abaixo do solo se concentram no estudo de micro-organismos, pois a maioria dos 32 trabalhos avaliados da RBCS abordavam interações abaixo e ou acima do solo a partir de estudos com micro-organismos (SILVA et al, 2010;GIONGO et al, 2010;MARTINS ET AL, 2010), principalmente a biomassa microbiana que tem sido o principal componente utilizado para avaliar a qualidade e a atividade biológica do solo (ZILLI et al, 2003), isso devido a grande evolução científica pela qual tem passado os estudos com marcadores moleculares (FIGUEIREDO et al, 2008;GOULART et al, 2011) que são determinantes na identificação filogenética e mesmo taxonômica dos organismos presentes na biomassa microbiana e também na fauna do solo, e também pela maior sensibilidade desses organismos as alterações ocorridas no ambiente ao longo do espaço e do tempo.…”
Section: Desenvolvimentounclassified